Community structure and estimation of aboveground biomass and carbon stock of beach forest in Carles, Iloilo, Philippines - Roldan, Dea C. (2016.)
Beach forests have long been forgotten or even ignored in mainstream science for a long period of time. It is only fairly recently that their role in mitigating the impacts of climate change are again gaining attention. Beach forest trees are able to prevent coastal erosion and shows an adaptation to salt spray, high temperature and radiation as well as mobile substrates. Unfortunately, little is known about them in terms of diversity, ecology and distribution that makes this study useful. This study aimed to assess the community structure and estimate the carbon stock and aboveground biomass of beach forest in Barangay Puta, Carles, Iloilo, Philippines. Specifically, it aimed to: a) Identify the beach forest species present in the area; b) Describe the community structure in terms of: species composition, diameter at breast height and stand height, stand basal area, importance value, index of biodiversity, species richness and evenness; c) Determine aboveground biomass and carbon stock; and d) Determine whether there is a relationship between beach forest species mean DBH and carbon stock and between mean height and carbon stock. A field survey was conducted using five (5) 100 m transect line with 3 sub- plots each on February 6-8, 2016. Results showed a total of 63 beach forest species belonging to 30 families were identified. Family Fabacaeae ranked first with 10 species, followed by Euphorbiaceae Apocynaceae with 8 and 7 species, respectively. Cocos nucifera recorded the highest value basal area (27.49), relative dominance (45.66%), relative frequency (11.69%) and importance value of 62.97. Average biomass was 259.6 tons/ha and estimated to contain 129.8 tons/ha carbon stock. The beach forest in the surveyed sites showed a relatively high diversity at H? = 1.24 and high amount of above ground carbon stock useful in mitigating the impacts of climate. There is an urgent need to protect, preserve and conserve the areas for the benefit of future generations.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Biomass -- Brgay. Puta, Carles, Iloilo; Beach forest -- Brgay. Puta, Carles, Iloilo; Community structure -- Beach forest -- Brgay. Puta, Carles, Iloilo; Carbon Sctock -- Beach forest -- Brgay. Puta, Carles, Iloilo